Dos correcciones a inscripciones romanas de Galicia (Catoira y Rodeiro, Pontevedra. Hispania Citerior) - Abascal Palazón, Juan Manuel, 1958- (2021)
Nueva publicación de un altar de Catoira y de un grafito de Rodeiro, en ambos casos para corregir las lecturas precedentes. El altar de Catoira no es votivo sino funerario y desvela la presencia en Galicia del nombre personal Pietas. El grafito de Rodeiro contiene una advertencia contra ladrones mediante el empleo del verbo paedico.
New publication of an altar from Catoira and a graphite from Rodeiro, in both cases to correct previous readings. The altar of Catoira is not votive but funerary and reveals the presence in Galicia of the personal name Pietas. Rodeiro’s graphite contains a warning against thieves and shows the use of the verb paedico.
Keywords: Inscripciones latinas; Península Ibérica